2022
DOI: 10.1108/ijbpa-03-2022-0041
|View full text |Cite
|
Sign up to set email alerts
|

Sustaining modern heritage buildings: visual defect categorisation guides for the general condition survey of rendered-painted facades

Abstract: PurposeRegular inspection and maintenance is recommended to preserve and sustain built cultural heritage. Systematising inspection processes and knowledge on defects, and providing pictorial guides for evaluating defects is an approach that may facilitate their condition survey. Generating pictorial guides for preliminary visual inspection of Modern Heritage buildings with rendered-painted facade concerning two defects (i.e. crack and efflorescence) is aimed in this study. These guides are thought as aids in d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…There are studies on the defects that are either generally observed in the buildings (Abbott, McDuling, Parsons, & Schoeman, 2007;Faqih, Zayed, & Soliman, 2020;Guo, Wang, & Li, 2021;Macarulla et al, 2013;Richardson, 2002) or specifically on the façade (Amaro, Saraiva, de Brito, & Flores-Colen, 2013;Çelik, Ergin, Dal, & Ay, 2023;Ertemir & Edis, 2022;Pereira, Silva, Brito, & Silvestre, 2020), and some of them consider heritage value too. Amaro et al (2013) and Pereira et al (2020) offer methods for inspection and diagnosis of defects on the wall covered with thermal insulation composite system and rendered façade, respectively.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…There are studies on the defects that are either generally observed in the buildings (Abbott, McDuling, Parsons, & Schoeman, 2007;Faqih, Zayed, & Soliman, 2020;Guo, Wang, & Li, 2021;Macarulla et al, 2013;Richardson, 2002) or specifically on the façade (Amaro, Saraiva, de Brito, & Flores-Colen, 2013;Çelik, Ergin, Dal, & Ay, 2023;Ertemir & Edis, 2022;Pereira, Silva, Brito, & Silvestre, 2020), and some of them consider heritage value too. Amaro et al (2013) and Pereira et al (2020) offer methods for inspection and diagnosis of defects on the wall covered with thermal insulation composite system and rendered façade, respectively.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Amaro et al (2013) and Pereira et al (2020) offer methods for inspection and diagnosis of defects on the wall covered with thermal insulation composite system and rendered façade, respectively. On the other hand, Ertemir & Edis (2022) develops an inspection approach, especially for the rendered-painted façade defects in modern period mass housing.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…For architectural surfaces, a common approach for defining their conservation states consist of the production of decay maps based on visual surveys in accordance with specific norms [28,29]. Decay indexes are then associated based on an empirical parameterization of observed decay features [30][31][32][33][34]. This approach is quite convenient for investigating single or small groups of buildings, but it is difficult to apply at an urban scale due to issues related to time and available resources.…”
Section: Introductionmentioning
confidence: 99%
“…Dilruba Ya gmur Ertemir and Ecem Edis authored a contribution entitled "Sustaining modern heritage buildings: visual defect categorisation guides for the general condition survey of rendered-painted facades" (Ertemir and Edis, 2023). The authors argue that regular inspection and maintenance is recommended to preserve and sustain built cultural heritage.…”
mentioning
confidence: 99%